Respuesta :
Answer:
x = -11
Step-by-step explanation:
1. Distribute 3 to the parenthesis and distribute 5 to the parenthesis
3x-12 = 5x + 10
2. Combine like terms (subtract 3x on both sides and then subtract 10 on both sides)
2x = -22
3. Divide both sides by 2
x = -11
please give me brainliest if this helped
Answer:
x=−11
Step-by-step explanation:
3(x-4)=5(x+2)
Simplify both sides of the equation:
3(x−4)=5(x+2)
(3)(x)+(3)(−4)=(5)(x)+(5)(2)(Distribute)
3x−12=5x+10
Subtract 5x from both sides
−2x−12=10
add 12 to both sides
−2x=22
Divide by -2 both sides
x=−11
Hope this helps.